2004
DOI: 10.1111/j.1365-2354.2004.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Deprivation, comorbidity and survival in a cohort of patients with colorectal cancer

Abstract: We studied a regionally based cohort of 483 consecutive patients with colorectal cancer referred for chemotherapy and/or radiotherapy. These patients were assessed and managed according to consistent policies. We investigated the effects of socio-economic deprivation and comorbidity upon survival. Significant comorbidity was present in 48% of the patients. Overall survival and cause-specific survival were summarized using Kaplan-Meier curves. Equality of survivor functions was assessed using the logrank proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 17 publications
4
15
1
Order By: Relevance
“…A number of studies have found an association between the Charlson index and survival among colon cancer patients [4,12,14,44,46]. The Charlson index is a well established tool for summarising comorbidity; however there are problems with its use.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found an association between the Charlson index and survival among colon cancer patients [4,12,14,44,46]. The Charlson index is a well established tool for summarising comorbidity; however there are problems with its use.…”
Section: Discussionmentioning
confidence: 99%
“…Delay between referral and treatment was similar across all social classes and so did not explain the findings. Although this study did not adjust for comorbidity, another Scottish study which had done so also found poorer survival in colorectal cancer patients from the most deprived socioeconomic quintiles, in a study population which showed no correlation between socioeconomic deprivation and co-morbidity[10]. The findings of these studies, in the UK healthcare setting where access to treatment is equal and free, suggest that decision-making (by both physicians and patients) regarding chemotherapy may be influenced by non-clinical factors.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity has not, so far, been examined in relation to international differences in survival. Although it has been considered as a possible explanation for differences in survival between socio-economic groups, [50][51][52] it has received relatively little attention to date. The investigation of patterns of care in relation to preexisting comorbidity should be a priority for future research.…”
Section: Possible Causal Explanationsmentioning
confidence: 99%